The Bangladesh registration manual, 1983 - Bangladesh; Bangladesh; Bangladesh (Dhaka : Deputy Controller, Govt. Print. Press, 1984)
Incorporates Registration Act, 1908, as amended and applicable to Bangladesh and Bangladesh Registration Rules, 1973.
"Published by Authority."
Keywords: Recording and registration -- Bangladesh